The Interplay Between Chromatin Architecture and Lineage-Specific Transcription Factors and the Regulation of Rag Gene Expression - Miyazaki, Kazuko; Miyazaki, Masaki (Frontiers in Immunology, 2021)
Cell type–specific gene expression is driven through the interplay between lineage-specific transcription factors (TFs) and chromatin architecture, such as topologically associating domains (TADs) and enhancer-promoter interactions. To elucidate the molecular mechanisms of the cell fate decision and cell type-specific function, it is important to reveal how chromatin architectures and TFs interplay and dictate cell lineage commitment. Together with the chromatin architectures, promoter and regulatory elements control gene expression. Among regulatory elements, super-enhancer (SE) plays a key role in establishing cell identity. Adaptive immunity relies on the Rag-mediated assembly of antigen recognition receptors. Hence, the regulation of the Rag1 and Rag2 genes is a hallmark of adaptive lymphoid lineage commitment. Here, we review the current knowledge of the 3D genome organization, SE formation, and Rag1/2 gene regulation during B and T cell differentiation.